2007
DOI: 10.1073/pnas.0610383104
|View full text |Cite
|
Sign up to set email alerts
|

DEC-205 receptor on dendritic cells mediates presentation of HIV gag protein to CD8 + T cells in a spectrum of human MHC I haplotypes

Abstract: Optimal HIV vaccines should elicit CD8 ؉ T cells specific for HIV proteins presented on MHC class I products, because these T cells contribute to host resistance to viruses. We had previously found that the targeting of antigen to dendritic cells (DCs) in mice efficiently induces CD8 ؉ T cell responses. To extend this finding to humans, we introduced the HIV p24 gag protein into a mAb that targets DEC-205/CD205, an endocytic receptor of DCs. We then assessed cross-presentation, which is the processing of nonre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
184
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(190 citation statements)
references
References 56 publications
2
184
1
3
Order By: Relevance
“…A fascinating recent example has been provided in the case of HIV gag protein delivered within antibodies to human DEC-205. For the first time, it has been shown that cross-presentation is able to extract defined peptides for presentation to CD8 + T cells across a spectrum of MHC haplotypes [94]. I am excited about this new field of receptor-based antigen targeting to DC, which allows one to analyze DC function -both antigen processing and subsequent interactions with lymphocytes -directly in vivo, without the need for cell isolation.…”
Section: New Developments In Antigen Handling and Maturation Of Dendrmentioning
confidence: 99%
“…A fascinating recent example has been provided in the case of HIV gag protein delivered within antibodies to human DEC-205. For the first time, it has been shown that cross-presentation is able to extract defined peptides for presentation to CD8 + T cells across a spectrum of MHC haplotypes [94]. I am excited about this new field of receptor-based antigen targeting to DC, which allows one to analyze DC function -both antigen processing and subsequent interactions with lymphocytes -directly in vivo, without the need for cell isolation.…”
Section: New Developments In Antigen Handling and Maturation Of Dendrmentioning
confidence: 99%
“…To assess the capacity of the 3D6 and 3G9 mAbs to mediate cross-presentation, we studied HIV-primed CD8 ϩ T cells from HIV-infected individuals as previously described, 11 since we were unable to prime large numbers of CD8 ϩ T cells to HIV Gag in Acetone-fixed cryostat sections of subcutaneous lymph nodes were stained with 3G9 mAb, followed by secondary PE-conjugated antihuman IgG, and FITC-anti-B220 to discriminate B and T areas. Images were taken 200ϫ magnification, but the region with the asterisk (*) is magnified 400ϫ on the right using a Molecular Devices OlympusAX70 deconvolution microscope (Olympus) running METAMORPH Meta Imaging 3.0 (Universal Imaging Corporaration).…”
Section: Cross-presentation Of Human Anti-hdec205 Hiv Gag To Gag Primmentioning
confidence: 99%
“…Nevertheless, these cell-based vaccines present some disadvantages, mainly related to their cost and the variability of the preparations between different patients. Engineered cell-free vaccine antigens that specifically target DC in vivo have also been used [24]. One of the most frequent approaches for vaccination in cancer is based on the use of 8-10 aa-long minimal MHC I-binding peptides derived from TAA.…”
mentioning
confidence: 99%